Mesoscopy a new approach for industrial in-line inspection. - Ide-ektessabi, Ari (Asean Engineering Journal)
In this paper we propose a system for in-line inspection of high precision production systems. Mesoscopes, in analogy with microscopes are systems that can visualize surface areas with dimensions of a few meters with the ability to bring into focus meso-structures of a few microns using visible light spectroscopy. We present systems developed at Kyoto University and discuss the potential applications in display production industry and cultural heritage investigations.